Qu’attendent les enseignants universitaires français en termes de formation et d’accompagnement pédagogiques ? - Joëlle Demougeot-Lebel; Cathy Perret (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Addressing and analysing needs is as essential step of curriculum and instructional design within the framework of faculty development units. This article studies educational and professional development needs established by French faculty through an inquiry. The purpose is to take into considerations specific aspects related to our context. The study indicates a low interest of faculty in answering the questionnaire but a high interest in educational development for those who take part. More precisely, if the respondents hold junior positions, their expectations do not differ from more experienced teachers. All express multiple needs basically related to the need to understand students, to relate to them easily or to overcome discomforted regarding teaching.